2021
DOI: 10.3390/catal11030340
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Bagasse Saccharification by Enzymatic Hydrolysis Using Endocellulase and β-glucosidase Immobilized on Different Supports

Abstract: The saccharification of sugarcane bagasse by enzymatic hydrolysis is one of the most promising processes for obtaining fermentable sugar to be used in the production of second-generation ethanol. The objective of this work was to study the immobilization and stabilization of two commercial enzymes: Endocellulase (E-CELBA) in dextran coated iron oxide magnetic nanoparticles activated with aldehyde groups (DIOMNP) and β-glucosidase (E-BGOSPC) in glyoxyl agarose (GLA) so that their immobilized derivatives could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…sugarcane bagasse). 16,[20][21][22][23][24][25] Various materials (organic or inorganic, nano or microporous) have been applied as supports for enzyme immobilization by different techniques. 19,26,27 These topics will be discussed in the following sections.…”
Section: Free Versus Immobilized Enzymesmentioning
confidence: 99%
“…sugarcane bagasse). 16,[20][21][22][23][24][25] Various materials (organic or inorganic, nano or microporous) have been applied as supports for enzyme immobilization by different techniques. 19,26,27 These topics will be discussed in the following sections.…”
Section: Free Versus Immobilized Enzymesmentioning
confidence: 99%
“…According to the authors, the incorporation of clay provided a support with greater adsorption capacity and greater rigidity (mechanical resistance), improving its performance. In the studies performed by Morais et al [84] in the immobilization of Endocellulase and β-glucosidase in magnetic iron oxide nanoparticles demonstrated that the enzymatic immobilization improved the thermal stability of the biocatalysts, achieving residual activities of 80% in 72 h of incubation at 60 • C.…”
Section: Effect Of Ph and Temperature On Immobilized Lipase Activitymentioning
confidence: 99%
“…Studies mainly involve the immobilization into preexisting materials and the evaluation of the influence of the material supports in the interplay with different immobilization chemistries. Catalytic properties as recovered activity and stability were evaluated [18][19][20][21][22][23][24][25][26]. Active immobilization by adsorption (anion exchange based ionic adsorption) or covalent binding (via aldehyde chemistry) to porous material supports have been shown as a promising strategy to obtain active and stable catalysts of different βglucosidases.…”
Section: Introductionmentioning
confidence: 99%
“…Active immobilization by adsorption (anion exchange based ionic adsorption) or covalent binding (via aldehyde chemistry) to porous material supports have been shown as a promising strategy to obtain active and stable catalysts of different βglucosidases. In these previous works, the focus of the immobilization design was obtaining high specific activity (similar to the free enzyme) and enhancing the stability under resting conditions, which represents a promising point for implementation [17,18,[24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%